Lauro de Oliveira Lima e a escola secundária: um estudo de sua produção intelectual ao longo de sua trajetória profissional (1945-1964) - Ando, Lia Marcia [UNIFESP] (2015)
This is an investigation about Lauro de Oliveira Lima?s proposal of pedagogical renovation of the secondary level (i.e., ?ginásio? and ?colégio?) during the 50?s and 60?s, taking for basis his intellectual production throughout his professional life. It deals with a didactic model formulated about Jean Piaget?s genetic epistemology theory, which has been denominated psychogenetic method. The proposal consisted on setting the student in an active and participative form within the learning process, instead of the traditional pedagogical system in which prevailed the teacher?s verbalism, and the memorization of the contents as well. Through work in groups, and with the use of researches and dynamic activities, the student was challenged to solve problem-situations in a sequential process of evolution, in order to develop feelings of solidarity, cooperation, and reciprocity, and to reach both maturing of thinking (until he could reache reflexive thought), and moral (until he could reach his autonomous phase). The method was developed and applied by his creator Lauro de Oliveira Lima, within the courses promoted by the Second Level Improvement Campaign (CADES), which prepared teachers for the exams that enabled them to give classes in secondary schools by the time of the expansion of this teaching level. The pedagogical proposal, which involved planning suggestions, administrative organization, curricula, material resources, evaluating process, and other issues, was propagated through Lauro de Oliveira Lima?s texts, that became periodic articles and books, as well, such as The modern secondary school: organization, methods and processes, which arrived to its eleventh edition. The study of such printings follows the principle of the Cultural History, in which the thinking of a certain author is not disconnected from his production conditions and diffusion, always being important the material way through what his ideas are vehiculated, for the materiality of its support also produces senses that must be considered. After occupying the highest rank in charge of the secondary teaching level within the Ministry of Education before the military coup, Lauro de Oliveira Lima changes his professional trajectory to business activities. Among such activities he funds an educational institution to apply the psychogenetic method to small children. From the middle of the 80?s, he was strongly influenced by the conceptions of Jean Piaget ? precisely during the period on which the scientist?s and his constructivism were most talked about, a lot linked to literacy and to the first levels of teaching. His presence and his name tended to vanish from the educational debates, and nowadays he is no longer a reference for teacher?s training, especially regarding to childhood education, as for the initial years of elementary education. The signs in his ideas and works ? secondary and method, as well ? were decisive for his trajectory.